Is halal a priority in purchasing cosmetics in Malaysia among Muslim Malaysian women - Kaur, Kamaljeet; Osman, Syuhaily; Sandhu, Sukjeet Kaur; Singh, Jaspal (Zes Rokman Resources, 2018)
This study is to investigate if the Malaysian Muslim women considers halal as an important attribute during the purchase of cosmetics. A total of 265 valid questionnaires were used to run to collect data via self-administrative questionnaires. A mall-intercept technique was used to carry out the survey. The data collection were collected in the two largest shopping mall surrounding Putrajaya which are Alamanda shopping Centre and the IOI City Shopping Mall. Results showed that halal was not the ultimate priority during the purchase of cosmetics by Malaysian Muslim women. This finding post for future researchers to further understand why halal is not taken as an utmost priority. Qualitative study using focus group or interviews would be deemed an effective method to understand the purchasing behavior of Malaysian Muslim women.